Safety of the Salmonella enterica serotype Dublin strain Sdu189-derived live attenuated vaccine—A pilot study - Wang, Fuzhong; Wang, Lei; Ge, Haojie; Wang, Xiaobo; Guo, Yaxin; Xu, Zhengzhong; Geng, Shizhong; Jiao, Xin'an; Chen, Xiang (Frontiers in Veterinary Science, 2022)
Salmonella enterica serovar Dublin (S. Dublin) is an important zoonotic pathogen with high invasiveness. In the prevention and control of the Salmonella epidemic, the live attenuated vaccine plays a very important role. To prevent and control the epidemic of S. Dublin in cattle farms, the development of more effective vaccines is necessary. In this study, we constructed two gene deletion mutants, Sdu189ΔspiC and Sdu189ΔspiCΔaroA with the parental strain S. Dublin Sdu189. The immunogenicity and protective efficacy were evaluated in the mice model. Firstly, both mutant strains were much less virulent than the parental strain, as determined by the 50% lethal dose (LD50) for specific pathogen-free (SPF) 6-week-old female BALB/c mice. Secondly, the specific IgG antibody level and the expression level of cytokine TNF-α, IFN-γ, IL-4, and IL-18 were increased significantly in the vaccinated mice compared to the control group. In addition, the deletion strains were cleared rapidly from organs of immunized mice within 14 d after immunization, while the parental strain could still be detected in the spleen and liver after 21 d of infection. Compared with the parental strain infected group, no obvious lesions were detected in the liver, spleen, and cecum of the deletion strain vaccinated groups of mice. Immunization with Sdu189ΔspiC and Sdu189ΔspiCΔaroA both provided 100% protection against subsequent challenges with the wild-type Sdu189 strain. These results demonstrated that these two deletion strains showed the potential as live attenuated vaccines against S. Dublin infection. The present study established a foundation for screening a suitable live attenuated Salmonella vaccine.